(untitled) (Concept: The Journal of Contemporary Community Education Practice Theory, 2017)
Violence against women is a worldwide yet still largely hidden problem. One in three women worldwide will experience physical or sexual violence in their lifetime’ (Walby, et al, 2017. 2). This matters. Violence wrecks lives (Ibid). But freedom from the threats of harassment and sexual assault are freedoms that so many women can hardly imagine, because violence is such a deep rooted aspect of so many cultures. These issues are becoming increasingly recognised for the social injustices and human rights violations that they are – and increasingly challenged. This has been especially so in India, following the national and indeed the international publicity that followed the horrific rape of a young woman in Delhi, in 2012. Although the victim subsequently died from her injuries, this was not before she had time to give evidence about the attack, and so to raise wider awareness of the urgent need for action in response.